Communities of mycorrhizal fungi in different trophic types of Asiatic Pyrola japonica sensu lato (Ericaceae) - Matsuda, Yosuke; Yamaguchi, Yusuke; Matsuo, Naoko; Uesugi, Takashi; Ito, Junko; Yagame, Takahiro; Figura, Tomáš; Selosse, Marc-André; Hashimoto, Yasushi (Journal of plant research, 2020)
Mixotrophic plants obtain carbon by their own photosynthetic activity and from their root-associated mycorrhizal fungi. Mixotrophy is deemed a pre-adaptation for evolution of mycoheterotrophic nutrition, where plants fully depend on fungi and lose their photosynthetic activity. The aim of this study was to clarify mycorrhizal dependency and heterotrophy level in various phenotypes of mixotrophic Pyrola japonica (Ericaceae), encompassing green individuals, rare achlorophyllous variants (albinos) and a form with minute leaves, P. japonica f. subaphylla. These three phenotypes were collected in two Japanese forests. Phylogenetic analysis of both plants and mycorrhizal fungi was conducted based on DNA barcoding. Enrichment in 13C among organs (leaves, stems and roots) of the phenotypes with reference plants and fungal fruitbodies were compared by measuring stable carbon isotopic ratio. All plants were placed in the same clade, with f. subaphylla as a separate subclade. Leaf 13C abundances of albinos were congruent with a fully mycoheterotrophic nutrition, suggesting that green P. japonica leaves are 36.8% heterotrophic, while rhizomes are 74.0% heterotrophic. There were no significant differences in δ13C values among organs in both albino P. japonica and P. japonica f. subaphylla, suggesting full and high mycoheterotrophic nutrition, respectively. Among 55 molecular operational taxonomic units (OTUs) detected as symbionts, the genus Russula was the most abundant in each phenotype and its dominance was significantly higher in albino P. japonica and P. japonica f. subaphylla. Russula spp. detected in P. japonica f. subaphylla showed higher dissimilarity with other phenotypes. These results suggest that P. japonica sensu lato is prone to evolve mycoheterotrophic variants, in a process that changes its mycorrhizal preferences, especially towards the genus Russula for which this species has a marked preference.
Keywords: Pyrola; mykorhiza; taxonomické DNA čárové kódování; Heterotrophic Processes; Mycorrhizae; Phylogeny; DNA Barcoding, Taxonomic; Rhizome; Japan; symbióza; oddenek; fylogeneze; Symbiosis; Plant Leaves; listy rostlin; heterotrofní procesy; Japonsko